Acute Tuberculous Appendicitis with Intestinal Obstruction - Yongkie Iswandi Purnama; I Dewa Nyoman Wibawa (The Indonesian Society for Digestive Endoscopy, 2019)
Tuberculosis (TB) can involve any organs. Tuberculous appendicitis is a rare case. Incidence of primary tuberculous appendicitis is 0.1-0.3% while incidence of secondary tuberculous appendicitis is 1.5-3%. Tuberculous appendicitis occurs in 0.08% of all appendectomy and 0.2% of all TB cases. We reported an acute tuberculous appendicitis with intestinal obstruction. Diagnosis was established based on histopathological findings. Treatments included appendectomy and first category of anti tuberculosis drugs (ATD) for 6 months. This case was reported to add our insight about possibility of TB as an etiology of many pathologic conditions in abdominal cavity.